Preparation and growth‐promoting effect of selenium nanoparticles capped by polysaccharide‐protein complexes on tilapia. (14th August 2020) - Ren, Lirong; Wu, Zhencong; Ma, Ying; Jian, Wenjie; Xiong, Hejian; Zhou, Lina
Abstract: BACKGROUND: Compared with traditional inorganic and organic selenium compounds, nano‐selenium exhibited higher biological safety and nutritional potency. However, the biological efficacy of nano‐selenium has not been comprehensively and accurately evaluated due to its dispersion instability. RESULTS: In this study, novel selenium nanoparticles (SeNPs) with high dispersion stability were successfully prepared using a polysaccharide‐protein complex (PSP) as the capping agent. This was isolated from abalone viscera. The average particle size and zeta potential of polysaccharide‐protein complex selenium nanoparticles (PSP‐SeNPs) were 63.33 nm, and −37.1 mV, respectively. The SeNPs were firmly capped by PSP through SeO and SeN bonds, as demonstrated by X‐ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, and transmission electron microscopy. Due to this capping, the dispersion of PSP‐SeNPs remained stable for 12 months at 4 °C, as evidenced by visual inspection and multiple light scattering. Furthermore, PSP‐SeNPs imparted an excellent growth‐promoting effect on tilapia. The FBW, WGR, and SGR values of tilapia juveniles fed with PSP‐SeNPs supplemented diets (0.5–4.5 mg/kg) were significantly higher than those of the control ( P < 0.05). A weight gain rate of 4.1%–43.4% and specific growth rate of 0.15%–1.74% were obtained in tilapia during 45‐day feeding. CONCLUSIONS: The use of marine viscera polysaccharides is a promising, green method for the synthesis of selenium nanoparticles. There are good opportunities for the application of the synthesized PSP‐SeNPs in the life sciences. © 2020 Society of Chemical Industry